KONTEKSTUALISASI MUNĀSABAH PADA TAFSIR MUSHAFÎ DAN TAFSIR NUZÛLÎ: Analisis komparatif antara tafsir Tarti>b al-Mus}h}af dan tafsir Tarti>b al-Nuzu>l. - Abu Bakar Bakar (Dialogia, 2016)
Abstract: Qur'an has a multi-dimensional, ranging from rational empirical dimension to mystical dimension of spiritual-emotional. One empirical dimension of Qur'an is a form of text that can be seen, read, studied and understood. While mystical and spiritual emotional dimensions are irrational. Empirical studies of Qur’an are often faced with its historical problem self. Because that rational is irrelevance with historical facts.   To rationalize the discrepancy between empirical and historical facts, al-muna>sabah are conducted. Furthermore, Qur'an also has a historical fact, such historically strategic position in declining Qur’an continuously. In fact, history facts of Qur’an are more strength than empirical ones (manuscripts orderly). According to the fact above, this study focuses on the application of muna>sabah towards tartîb al-mus}h}af and tartîb al-nuzu>l  in interpreting surah and those results. This study conducted inductive-deductive approach and method.It can be summed up that 1). Interpreting surah in tafsir mushaî  by using muna>sabah can be done detail and musfassir concerns on munasabah of the whole elements in Qur’an. While, in tafsir nuzu>li>, muna>sabah  could be done though recording the continuum of surah.  the aim is to show the whole content of Qur’an in order not to be understood partially. Munāsabah in tafsir mushafî is structural-emotional, while munāsabah in tafsir nuzûlî has ratinal-cultural pattern 2). Interpreting surah by using munāsabah approach in tafsir mushafî produces rational relation among the elements in Qur’an. While in the tafsir nuzûlî, it emphases on the strengthen of history and the records.Even they differ; both perform similar steps such other commentators done. They do not lead unclear and unequivocal interpretation suspicious to the conclusion that a clear and interpretation, except only reinforces the dominant idea in the previous theories Keywords: munāsabah, tafsi>r mus}h}afī, tafsi>r nuzu>li